Superfine all-tailing filling paste water reducing agent as well as preparation method and application thereof
The ultrafine full-tailed sand-filled paste water reducer prepared by using raw materials such as ethylene glycol monovinyl polyethylene glycol ether and hydroxypropyl methyl cellulose, the existing polycarboxylic acid water reducer is solved in the treatment of ultra-fine polycarboxylic acid water reducer The long synthesis time and poor economic benefits of fine full-tailed sand have achieved efficient improvement in compressive strength and stability of fillers. It is suitable for multiple types of ultra-fine full-tailed sand and supports the sustainable development of green mines.
Patent Information
- Application Number
- CN202411202274.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-29
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-08-29
AI Technical Summary
The existing polycarboxylic acid water reducing agents are synthesised for a long time, high reaction temperature and poor economic benefits when treating ultrafine full tailings sand. It is difficult to effectively improve the compressive strength and stability of the filler, and are not suitable for many types of ultrafine full tailings sand. The application of the sand tailings and the construction of green mines.
The mother liquor was prepared by ethylene glycol monovinyl polyethylene glycol ether as a large monomer, and the viscosity and dosage were optimized by adding hydroxypropyl methylcellulose, and combined with chain transfer agent, oxidant and reducing agent, a kind was prepared. The new ultra-fine full-tailed sand-filled paste water reducing agent has a short synthesis time, a low reaction temperature and good economic benefits, which can significantly improve the compressive strength and stability of the filling.
It realizes efficient treatment of ultra-fine full-tailed sand filling paste, reduces cement usage and material cost, improves the flowability and strength of the filling body, and is suitable for different types of ultra-fine full-tailed sand, supporting the sustainability of green mines. develop.
Smart Images

Figure CN119219359A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of mine tailings filling, and relates to an ultra-fine full tailings filling paste water reducing agent and a preparation method and application thereof. Background Art
[0002] Underground mining is widely used in the excavation and extraction of valuable mineral resources, but this inevitably produces a large amount of waste tailings. At the same time, these waste minerals are usually piled up on the surface in a low-cost way to build dams to block the valley mouth, which not only easily brings huge safety hazards (tailings dam landslides, earthquakes, etc.), but also has adverse effects on the environment (heavy metal leaching and groundwater pollution, etc.). In this regard, the use of full tailings filling goaf technology can effectively solve the above problems. While alleviating the problem of tailings discharge and storage, it can also fully realize the comprehensive utilization of waste mineral resources. It is one of the important supporting technologies for green mine construction.
[0003] According to the classification of filling tailings in "Theory and Engineering of Cemented Filling of Metal Mines", it is generally believed that tailings with a -74μm particle content greater than 80%, a -19μm particle content greater than 50% and an average particle size less than 19μm are ultra-fine tailings. However, when ultra-fine tailings are treated with full tailings filling goaf technology, the filling effect is usually poor. This is not only because the ultra-fine tailings slurry is difficult to dehydrate, but also because of the large specific surface area. The filling materials made of ultra-fine tailings are often more viscous, have poor water retention, and have low strength after hardening. This seriously restricts the promotion and application of this technology. For this reason, domestic and foreign scholars often pre-classify or desludge the ultra-fine tailings, fill the resulting coarse-grained tailings into the underground goaf, and return the fine-grained tailings to the tailings pond through pipelines. This not only significantly reduces the utilization rate of tailings, but also seriously hinders the construction of green tailing-free mines. In particular, in recent years, with the reduction of high-quality mineral resources, in order to ensure sufficient metal recovery rate, ultrafine grinding technology has been widely used to process low-grade complex ores, resulting in the generation of a large amount of ultrafine tailings. Therefore, how to effectively treat ultrafine tailings is an urgent problem to be overcome at this stage.
[0004] Water reducer is an essential admixture in concrete for the construction industry. It can significantly improve the fluidity of concrete, control the setting or hardening time, increase the strength of concrete and improve workability. It is also considered to be an effective method to improve the concentration, workability and strength of ultrafine tailings filling slurry. Currently, common water reducers include naphthalene-based water reducers, melamine water reducers, lignin sulfonate water reducers and polycarboxylic acid water reducers. Among them, polycarboxylic acid water reducers have the advantages of low dosage, high water reduction rate, small slump loss and good cement applicability, and are currently the most widely used water reducers. However, the common polycarboxylic acid water reducers on the market are usually synthesized from methyl allyl polyethylene glycol ether (HPEG) macromonomers and isopentenyl polyethylene glycol ether (TPEG) macromonomers. These raw materials have low synthesis efficiency and high reaction temperature, resulting in high synthesis costs, which not only increases the cost of tailings filling, but also is not conducive to the green and sustainable economic development of mines. However, the existing water-reducing agent for tailings filling does not involve application research suitable for multiple types of ultrafine whole tailings and low-cost water-reducing agent synthesis methods. According to the previous research of the inventor of this application, the use of the existing polycarboxylic acid water-reducing agent synthesized from HPEG macromonomer and TPEG macromonomer is often accompanied by problems such as high dosage and early strength loss of the filling body. In particular, due to the high content of ultrafine particles in ultrafine tailings, it is difficult for the existing polycarboxylic acid water-reducing agent to effectively reduce the amount of cement in the full tailings filling paste, which seriously affects the processing efficiency of tailings and is not conducive to reducing material costs and tailings processing costs. The existence of the above defects indicates that the existing polycarboxylic acid water-reducing agent may not be suitable for processing ultrafine whole tailings. Therefore, it is of great significance to develop a new water-reducing agent with short synthesis time, low reaction temperature, good economic benefits, good particle size applicability, good operability, and the ability to significantly improve the compressive strength and stability of the filling body, which is effective in improving the filling effect of ultrafine tailings, and achieving cost reduction and efficiency improvement and improving the applicability of mine tailings, cementitious materials and proportions. Summary of the invention
[0005] The technical problem to be solved by the present invention is to overcome the shortcomings of the prior art and provide an ultrafine full tailings filling paste water reducer with short synthesis time, low reaction temperature, good economic benefit, good applicability, good operability, and the ability to significantly improve the compressive strength and stability of the filling body, as well as a preparation method and application thereof.
[0006] In order to solve the above technical problems, the present invention adopts the following technical solutions:
[0007] An ultra-fine full tailings filling paste water reducing agent comprises the following raw material components in parts by weight:
[0008] 60 to 120 parts of mother liquor,
[0009] Hydroxypropyl methylcellulose 0.08 to 0.12 parts;
[0010] The mother liquor is prepared by taking ethylene glycol monovinyl polyethylene glycol ether as a macromonomer; the viscosity of the hydroxypropyl methylcellulose is 60000MPa·s to 80000MPa·s.
[0011] The above-mentioned ultrafine full tailings filling paste water reducer is further improved, and the raw material components of the ultrafine full tailings filling paste water reducer are composed of mother liquor and hydroxypropyl methylcellulose.
[0012] The above-mentioned ultrafine full tailings filling paste water reducer is further improved in that the mother liquor is prepared with ethylene glycol monovinyl polyglycol ether, acrylic acid, chain transfer agent, oxidant and reductant as raw materials.
[0013] The above-mentioned ultra-fine full tailings filling paste water reducing agent is further improved in that the acid-ether ratio of the acrylic acid to ethylene glycol monovinyl polyglycol ether is 5.5-8.5:0.8-1.2.
[0014] The above-mentioned ultrafine full tailings filling paste water reducing agent is further improved, and the dosage of the chain transfer agent is 0.6% to 1% of the mass of the ethylene glycol monovinyl polyglycol ether.
[0015] The above-mentioned ultra-fine full tailings filling paste water reducing agent is further improved in that the dosage of the oxidant is 1.2% to 1.8% of the mass of the ethylene glycol monovinyl polyglycol ether.
[0016] The above-mentioned ultra-fine full tailings filling paste water reducing agent is further improved in that the amount of the reducing agent is 0.12% to 0.28% of the mass of the ethylene glycol monovinyl polyglycol ether.
[0017] The above-mentioned ultra-fine full tailings filling paste water reducer is further improved, and the chain transfer agent is at least one of thioglycolic acid, isopropanol, and mercaptoethanol.
[0018] The above-mentioned ultra-fine full tailings filling paste water reducer is further improved, and the oxidant is at least one of ammonium persulfate, hydrogen peroxide, and potassium peroxide.
[0019] The above-mentioned ultrafine full tailings filling paste water reducer is further improved, and the reducing agent is at least one of L-ascorbic acid, sodium sulfite, ferrous sulfate, and sodium bisulfite.
[0020] The above-mentioned ultra-fine full tailings filling paste water reducing agent is further improved, and the preparation method of the mother solution comprises the following steps:
[0021] (1) preparing liquid A with acrylic acid; preparing liquid B with a chain transfer agent and a reducing agent;
[0022] (2) Ethylene glycol monovinyl polyethylene glycol ether and an oxidant are mixed and stirred, and liquid A and liquid B are added dropwise to obtain a mother solution.
[0023] The above-mentioned ultrafine full tailings filling paste water reducer is further improved. In step (1), the A liquid is prepared by mixing acrylic acid and water; the B liquid is prepared by the following method: a chain transfer agent and a reducing agent are mixed with water, and ultrasonicated for 5 minutes to 10 minutes to obtain the B liquid.
[0024] The above-mentioned ultrafine full tailings filling paste water reducing agent is further improved. In step (2), the stirring is carried out at a temperature of 20°C to 40°C; the stirring time is 1min to 3min; and the dripping time of the A liquid and the B liquid is controlled at 0.5h to 3h.
[0025] As a general technical concept, the present invention also provides a method for preparing the above-mentioned ultra-fine full tailings filling paste water reducer, comprising the following steps: mixing the mother liquor with hydroxypropyl methylcellulose to obtain the ultra-fine full tailings filling paste water reducer.
[0026] As a general technical concept, the present invention also provides an application of the above-mentioned ultrafine full tailings filling paste water reducer or the ultrafine full tailings filling paste water reducer prepared by the above-mentioned preparation method in treating ultrafine full tailings filling paste.
[0027] The above application is further improved, and the application includes the following steps: mixing the ultrafine full tailings filling paste water reducer with the ultrafine full tailings filling paste to complete the treatment of the ultrafine full tailings filling paste; the amount of the ultrafine full tailings filling paste water reducer is 0.06% to 0.08% of the total mass of the ultrafine full tailings filling paste.
[0028] The above application is further improved, wherein the ultrafine tailings filling paste is composed of ultrafine tailings, cement and water; the content of -19μm particle size in the ultrafine tailings is greater than 50%, the content of -74μm particle size is greater than 80%, and D 50 <19μm.
[0029] Compared with the prior art, the advantages of the present invention are:
[0030] (1) In view of the defects of the existing polycarboxylic acid water-reducing agent, such as long synthesis time, high reaction temperature, poor economic benefit, poor applicability, poor operability, and difficulty in effectively improving the compressive strength and stability of the filling body, the present invention provides an ultra-fine full tailings filling paste water-reducing agent, which uses ethylene glycol monovinyl polyethylene glycol ether as a macromonomer, has an unsaturated C=C bond and forms a p-π conjugated bond with an O atom, so that the double bond electron cloud is greatly offset, thereby resulting in a higher polymerization activity. Therefore, using ethylene glycol monovinyl polyethylene glycol ether (EPEG) as a raw material, the water-reducing agent of the present invention has the advantages of short synthesis time, low reaction temperature, and good economic benefit. At the same time, the mother liquor prepared by using ethylene glycol monovinyl polyethylene glycol ether (EPEG) as a macromonomer can improve the fluidity of the filling paste, reduce the water consumption, and reduce the cement consumption, thereby reducing the cost. On this basis, by adding hydroxypropyl methylcellulose and optimizing hydroxypropyl methylcellulose, the present invention can improve the fluidity of the filling paste, reduce the water consumption, and reduce the cement consumption. The amount of propyl methylcellulose used can utilize the bridging effect between hydroxypropyl methylcellulose and the matrix to prevent the formation of voids and cracks inside the filling body, or change its extension direction. At the same time, hydroxypropyl methylcellulose will also promote the hydration of the cementitious material and increase the bonding strength. On the one hand, it can effectively improve the uniaxial compressive strength and stability of the filling paste, which is beneficial to improve the compressive strength of the filling paste. On the other hand, according to the particle size distribution characteristics of ultrafine whole tailings, by optimizing the viscosity of hydroxypropyl methylcellulose to 60000MPa·s~80000MPa·s, the cementing properties of the water reducer can be effectively improved, so that the water reducer can effectively bond ultrafine whole tailings of different particle sizes together. In particular, when the ultrafine particle content in the ultrafine tailings is high, it can also ensure that the filling paste has sufficient cementing properties, and at the same time, it can also effectively avoid the adverse effect of the high viscosity of hydroxypropyl methylcellulose on the strength of the hardened paste. In addition, when the dosage of hydroxypropyl methylcellulose is too high, the viscosity of the paste will be significantly increased, its fluidity will be reduced, and the construction difficulty will be increased; when the dosage of hydroxypropyl methylcellulose is too low, the less hydroxypropyl methylcellulose is not enough to prevent the formation of voids inside the filling body, thereby affecting the uniaxial compressive strength of the filling body. Compared with conventional polycarboxylic acid water reducers, the ultrafine full tailings filling paste water reducer of the present invention has the following advantages: (a) the required synthesis time is short, the reaction temperature is low, and it has good economic benefits. (b) The synthesis steps are simple, it is easily soluble in water, non-toxic and harmless, and friendly to the environment and construction personnel. (c) It can adapt to different types of ultrafine full tailings and has strong versatility. (d) It can significantly increase the concentration of ultrafine full tailings filling paste, reduce the ash-sand ratio, and improve fluidity and strength and operability while greatly reducing water consumption. (e) It can reduce the amount of cement in the ultrafine full tailings filling paste, increase the tailings consumption, while maintaining or improving the slurry performance, which helps to save material costs and tailings treatment costs.The ultrafine full tailings filling paste water reducer of the present invention has the advantages of short synthesis time, low reaction temperature, good economic benefit, good applicability, good operability, and the ability to significantly improve the compressive strength and stability of the filling body. It is a new type of water reducer with excellent performance, can be widely used in ultrafine tailings filling, can achieve effective filling of ultrafine tailings, has high use value, and good application prospects, and is of great significance for achieving cost reduction and efficiency improvement, as well as green sustainable economic development.
[0031] (2) The present invention also provides an application of an ultrafine full tailings filling paste water reducer in the treatment of ultrafine full tailings filling paste, specifically: the ultrafine full tailings filling paste water reducer is mixed with the ultrafine full tailings filling paste. Under the action of the water reducer, the expansion degree and compressive strength of the filling body can be effectively improved under the conditions of high solid concentration and low ash-sand ratio, which is of great significance for achieving effective treatment of ultrafine full tailings.
[0032] (3) In the present invention, by optimizing the dosage of the ultrafine full tailings filling paste water reducer to 0.06% to 0.08% of the total mass of the ultrafine full tailings filling paste, it is beneficial to improve the fluidity of the filling paste, and can avoid the problems of increased bubbles, increased viscosity, decreased strength and prolonged coagulation time caused by excessive dosage, as well as the problems of insufficient fluidity, construction difficulties and poor strength caused by too low dosage, and can reduce material costs, thereby achieving dual optimization of performance and economic benefits. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] In order to make the purpose, technical solution and advantages of the embodiments of the present invention more clear, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the accompanying drawings in the embodiments of the present invention.
[0034] Figure 1 This is a particle size distribution diagram of the ultrafine whole tailings in Example 1 of the present invention.
[0035] Figure 2 This is a state diagram of the ultra-fine full tailings filling paste without adding a water reducing agent in Example 1 of the present invention.
[0036] Figure 3 This is a state diagram of the ultrafine full tailings filling paste after adding a water reducer in Example 1 of the present invention. DETAILED DESCRIPTION
[0037] The present invention is further described below in conjunction with the accompanying drawings and specific preferred embodiments, but the protection scope of the present invention is not limited thereby.
[0038] Example 1
[0039] An ultra-fine full tailings filling paste water reducing agent comprises the following raw material components in parts by weight:
[0040] 60 parts of mother liquor,
[0041] Hydroxypropyl methylcellulose 0.1 parts.
[0042] In this embodiment, the raw material components of the ultra-fine full tailings filling paste water reducer are composed of mother liquor and hydroxypropyl methylcellulose.
[0043] In this embodiment, the mother liquor used is prepared using ethylene glycol monovinyl polyethylene glycol ether as a macromonomer, specifically: it is prepared using ethylene glycol monovinyl polyethylene glycol ether (EPEG), acrylic acid (AA), a chain transfer agent, an oxidant and a reducing agent as raw materials, wherein the chain transfer agent is thioglycolic acid (TGA), the oxidant is ammonium persulfate (APS), and the reducing agent is L-ascorbic acid (Vc).
[0044] In this embodiment, the method for preparing the mother solution comprises the following steps:
[0045] (1) Acrylic acid is prepared into liquid A, specifically, acrylic acid is mixed with an appropriate amount of deionized water to prepare liquid A. A chain transfer agent and a reducing agent are prepared into liquid B, specifically, thioglycolic acid, L-ascorbic acid are mixed with an appropriate amount of deionized water, and ultrasonicated for 10 minutes to obtain liquid B.
[0046] (2) Ethylene glycol monovinyl polyethylene glycol ether and ammonium persulfate are placed in a beaker and stirred in a constant temperature magnetic stirrer. The temperature is controlled at 20° C. during the stirring process. After stirring for 1 minute, liquid A and liquid B are added dropwise at the same time using a constant flow pump. The dropping time is controlled at 1.5 hours to obtain a yellow, thick mother liquor.
[0047] In this embodiment, during the preparation of the mother liquor, the acid-ether ratio of acrylic acid (AA) to ethylene glycol monovinyl polyethylene glycol ether (EPEG) is 5.5:1; the amount of thioglycolic acid (TGA) is 0.6% by mass of ethylene glycol monovinyl polyethylene glycol ether; the amount of ammonium persulfate (APS) is 1.5% by mass of ethylene glycol monovinyl polyethylene glycol ether; and the amount of L-ascorbic acid (Vc) is 0.2% by mass of ethylene glycol monovinyl polyethylene glycol ether.
[0048] In this embodiment, the viscosity of hydroxypropyl methylcellulose is 70000 MPa·s.
[0049] A method for preparing the above-mentioned ultra-fine full tailings filling paste water reducer comprises the following steps: mixing a mother liquor with hydroxypropyl methylcellulose to obtain an ultra-fine full tailings filling paste water reducer.
[0050] In this embodiment, the copolymerization synthesis formula of the ultra-fine full tailings filling paste water reducer is as follows:
[0051]
[0052] In the above formula, a and b represent the molar ratio of two different monomers, and n represents the number of repeating units in the resulting copolymer.
[0053] An application of the above-mentioned ultrafine full tailings filling paste water reducer in the treatment of ultrafine full tailings filling paste is specifically: the ultrafine full tailings filling paste water reducer is mixed with the ultrafine full tailings filling paste to complete the treatment of the ultrafine full tailings filling paste, wherein the amount of the ultrafine full tailings filling paste water reducer is 0.08% of the total mass of the ultrafine full tailings filling paste.
[0054] In this embodiment, the ultrafine tailings filling paste is composed of ultrafine tailings, cement and water, wherein the content of -19 μm particle size in the ultrafine tailings in Example 1 is 65%, the content of -74 μm particle size is 84%, and the content of D 50 For 10 μm, Figure 1 shown.
[0055] The filling paste after adding the water reducing agent in Example 1 was tested, and the results are shown in Table 1.
[0056] Figure 2 This is a state diagram of the ultrafine full tailings filling paste (blank sample) without adding a water reducing agent in Example 1 of the present invention.
[0057] Figure 3 This is a state diagram of the ultrafine full tailings filling paste after adding a water reducer in Example 1 of the present invention.
[0058] Comparative Example 1
[0059] A water reducing agent is substantially the same as that in Example 1, except that hydroxypropyl methylcellulose is not added in Comparative Example 1.
[0060] Comparative Example 2
[0061] A water reducing agent is substantially the same as Example 1, except that in Comparative Example 2, ethylene glycol monovinyl polyethylene glycol ether (EPEG) is replaced by methyl allyl polyethylene glycol ether (HPEG).
[0062] Comparative Example 3
[0063] A water reducing agent is substantially the same as Example 1, except that in Comparative Example 3, ethylene glycol monovinyl polyethylene glycol ether (EPEG) is replaced by isopentenyl polyethylene glycol ether (TPEG).
[0064] Comparative Example 4
[0065] A preparation method of a polycarboxylate water reducer comprises the following steps: adding 380 parts of ethylene glycol monovinyl polyglycol ether macromonomer and 8 parts of methacrylamide into a reactor by weight, adding water and stirring, controlling the reaction temperature to 25°C until the monomer is completely dissolved, adding 2.4 parts of ammonium persulfate, stirring for 10 minutes, and then dripping a material I solution and a material II solution simultaneously, the dripping time is 2 hours, keeping the temperature at 25°C for 2 hours, adding an alkali solution to neutralize to a pH of 6 to 7, and preparing a polycarboxylate water reducer, wherein the material I solution is obtained by adding water to 12 parts of vinyl acetate and 23 parts of acrylic acid and stirring them uniformly, and the material II solution is obtained by adding water to 1.4 parts of sodium sulfite and 1.0 part of thioglycolic acid and stirring them uniformly.
[0066] Comparative Example 5
[0067] A water reducing agent is substantially the same as Example 1, except that in Comparative Example 5, the viscosity of hydroxypropyl methylcellulose is 40000 MPa·s.
[0068] Comparative Example 6
[0069] A water reducing agent is substantially the same as Example 1, except that in Comparative Example 6, the viscosity of hydroxypropyl methylcellulose is 90000 MPa·s.
[0070] The water reducing agents prepared in Comparative Examples 1-6 were used to treat the ultrafine full tailings filling paste. Except for the water reducing agents, other conditions were the same as those in Example 1.
[0071] The filling pastes after adding water reducing agent in Comparative Examples 1-6 were tested, and the results are shown in Table 1.
[0072] Table 1 Test results of filling pastes in Example 1 and Comparative Examples 1-5
[0073]
[0074] From Table 1 and Figure 2 , Figure 3 It can be seen that compared with the blank sample, when the solid concentration is increased by 2% and the lime-sand ratio is reduced by about 14%, the expansion of the paste obtained after adding the water reducer in Example 1 is increased by 79 mm (such as Figure 2 and Figure 3 ), the 7d compressive strength increased by 0.76MPa.s, and the 28d compressive strength increased by 1.04MPa.s.
[0075] It can be seen from Table 1 that compared with Comparative Example 1, Comparative Example 2 and Comparative Example 3, when the solid concentration and the lime-sand ratio are similar, the expansion of the filling paste obtained after adding the water reducer in Example 1 is increased by 17 mm, 24 mm, and 31 mm, respectively, the 7d compressive strength is increased by 1.11 MPa.s, 0.30 MPa.s, and 0.18 MPa.s, respectively, and the 28d compressive strength is increased by 1.23 MPa.s, 0.34 MPa.s, and 0.28 MPa.s, respectively.
[0076] As shown in Table 1, compared with Comparative Example 4, when the solid concentration and the lime-sand ratio are similar, the expansion of the filling paste obtained after adding the water reducer in Example 1 is increased by 19 mm, the 7d compressive strength is increased by 0.85 MPa.s, and the 28d compressive strength is increased by 0.54 MPa.s. In addition, the water reducer prepared in Example 1 requires fewer types of synthetic raw materials, simple steps, and greatly shortens the synthesis time.
[0077] It can be seen from Table 1 that compared with Comparative Examples 5 and 6, when the solid concentration and the lime-sand ratio are similar, the expansion of the filling paste obtained after adding the water reducer in Example 1 is increased by 15 mm and 25 mm, respectively, the 7d compressive strength is increased by 0.29 MPa.s and 0.17 MPa.s, respectively, and the 28d compressive strength is increased by 0.42 MPa.s and 0.31 MPa.s, respectively.
[0078] Example 2
[0079] An ultra-fine full tailings filling paste water reducing agent comprises the following raw material components in parts by weight:
[0080] 60 parts of mother liquor,
[0081] Hydroxypropyl methylcellulose 0.08 parts.
[0082] In this embodiment, the mother liquor used is prepared using ethylene glycol monovinyl polyethylene glycol ether as a macromonomer, specifically: it is prepared using ethylene glycol monovinyl polyethylene glycol ether (EPEG), acrylic acid (AA), a chain transfer agent, an oxidant and a reducing agent as raw materials, wherein the chain transfer agent is thioglycolic acid (TGA), the oxidant is ammonium persulfate (APS), and the reducing agent is L-ascorbic acid (Vc).
[0083] In this embodiment, the method for preparing the mother solution comprises the following steps:
[0084] (1) Acrylic acid is prepared into liquid A, specifically, acrylic acid is mixed with an appropriate amount of deionized water to prepare liquid A. A chain transfer agent and a reducing agent are prepared into liquid B, specifically, thioglycolic acid, L-ascorbic acid are mixed with an appropriate amount of deionized water, and ultrasonicated for 10 minutes to obtain liquid B.
[0085] (2) Ethylene glycol monovinyl polyglycol ether and ammonium persulfate are placed in a beaker and stirred in a constant temperature magnetic stirrer. The temperature is controlled at 30° C. during the stirring process. After stirring for 1 minute, liquid A and liquid B are added dropwise at the same time using a constant flow pump. The dropping time is controlled at 1 hour to obtain a yellow, thick mother liquor.
[0086] In this embodiment, during the preparation of the mother liquor, the acid-ether ratio of acrylic acid (AA) to ethylene glycol monovinyl polyethylene glycol ether (EPEG) is 5.5:1; the amount of thioglycolic acid (TGA) is 0.9% by mass of ethylene glycol monovinyl polyethylene glycol ether; the amount of ammonium persulfate (APS) is 1.4% by mass of ethylene glycol monovinyl polyethylene glycol ether; and the amount of L-ascorbic acid (Vc) is 0.2% by mass of ethylene glycol monovinyl polyethylene glycol ether.
[0087] In this embodiment, the viscosity of hydroxypropyl methylcellulose is 60000 MPa·s.
[0088] A method for preparing the above-mentioned ultra-fine full tailings filling paste water reducer comprises the following steps: mixing a mother liquor with hydroxypropyl methylcellulose to obtain an ultra-fine full tailings filling paste water reducer.
[0089] An application of the above-mentioned ultrafine full tailings filling paste water reducer in the treatment of ultrafine full tailings filling paste is specifically: the ultrafine full tailings filling paste water reducer is mixed with the ultrafine full tailings filling paste to complete the treatment of the ultrafine full tailings filling paste, wherein the amount of the ultrafine full tailings filling paste water reducer is 0.08% of the total mass of the ultrafine full tailings filling paste.
[0090] In this embodiment, the ultra-fine tailings filling paste is composed of ultra-fine tailings, cement and water, wherein the content of -19 μm particle size in the ultra-fine tailings is 70%, the content of -74 μm particle size is 87%, and the content of D 50 9μm.
[0091] The filling paste after adding the water reducing agent in Example 2 was tested, and the results are shown in Table 2.
[0092] Table 2 Test results of filling paste in Example 2
[0093] parameter unit blank Test measurement value Solid concentration % 61 63 Lime-sand ratio - 1:6 1:7 Water reducing agent concentration % 0 0.08 Expansion mm 232 314 7d compressive strength MPa.s 2.55 3.7 28d compressive strength MPa.s 3.27 4.92
[0094] Example 3
[0095] An ultra-fine full tailings filling paste water reducing agent comprises the following raw material components in parts by weight:
[0096] 80 parts of mother liquor,
[0097] Hydroxypropyl methylcellulose 0.1 parts.
[0098] In this embodiment, the mother liquor used is prepared using ethylene glycol monovinyl polyethylene glycol ether as a macromonomer, specifically: it is prepared using ethylene glycol monovinyl polyethylene glycol ether (EPEG), acrylic acid (AA), a chain transfer agent, an oxidant and a reducing agent as raw materials, wherein the chain transfer agent is thioglycolic acid (TGA), the oxidant is ammonium persulfate (APS), and the reducing agent is L-ascorbic acid (Vc).
[0099] In this embodiment, the method for preparing the mother solution comprises the following steps:
[0100] (1) Acrylic acid is prepared into liquid A, specifically, acrylic acid is mixed with an appropriate amount of deionized water to prepare liquid A. A chain transfer agent and a reducing agent are prepared into liquid B, specifically, thioglycolic acid, L-ascorbic acid are mixed with an appropriate amount of deionized water, and ultrasonicated for 10 minutes to obtain liquid B.
[0101] (2) Ethylene glycol monovinyl polyethylene glycol ether and ammonium persulfate are placed in a beaker and stirred in a constant temperature magnetic stirrer. The temperature is controlled at 25° C. during the stirring process. After stirring for 1 minute, liquid A and liquid B are added dropwise at the same time using a constant flow pump. The dropping time is controlled at 2 hours to obtain a yellow, thick mother liquor.
[0102] In this embodiment, during the preparation of the mother liquor, the acid-ether ratio of acrylic acid (AA) to ethylene glycol monovinyl polyethylene glycol ether (EPEG) is 8:1; the amount of thioglycolic acid (TGA) is 0.8% by mass of ethylene glycol monovinyl polyethylene glycol ether; the amount of ammonium persulfate (APS) is 1.7% by mass of ethylene glycol monovinyl polyethylene glycol ether; and the amount of L-ascorbic acid (Vc) is 0.25% by mass of ethylene glycol monovinyl polyethylene glycol ether.
[0103] In this embodiment, the viscosity of hydroxypropyl methylcellulose is 75000 MPa·s.
[0104] A method for preparing the above-mentioned ultra-fine full tailings filling paste water reducer comprises the following steps: mixing a mother liquor with hydroxypropyl methylcellulose to obtain an ultra-fine full tailings filling paste water reducer.
[0105] An application of the above-mentioned ultrafine full tailings filling paste water reducer in the treatment of ultrafine full tailings filling paste is specifically: the ultrafine full tailings filling paste water reducer is mixed with the ultrafine full tailings filling paste to complete the treatment of the ultrafine full tailings filling paste, wherein the amount of the ultrafine full tailings filling paste water reducer is 0.06% of the total mass of the ultrafine full tailings filling paste.
[0106] In this embodiment, the ultra-fine tailings filling paste is composed of ultra-fine tailings, cement and water, wherein the content of -19 μm particle size in the ultra-fine tailings is 63%, the content of -74 μm particle size is 81%, and the content of D 50 is 12μm.
[0107] The filling paste after adding the water reducing agent in Example 3 was tested, and the results are shown in Table 3.
[0108] Table 3 Test results of filling paste in Example 3
[0109] parameter unit blank Test measurement value Solid concentration % 63 65 Lime-sand ratio - 1:6 1:7 Water reducing agent concentration % 0 0.06 Expansion mm 256 337 7d compressive strength MPa.s 3.63 4.47 28d compressive strength MPa.s 4.88 5.51
[0110] Example 4
[0111] An ultra-fine full tailings filling paste water reducing agent comprises the following raw material components in parts by weight:
[0112] 110 parts of mother liquor,
[0113] Hydroxypropyl methylcellulose 0.08 parts.
[0114] In this embodiment, the mother liquor used is prepared using ethylene glycol monovinyl polyethylene glycol ether as a macromonomer, specifically: it is prepared using ethylene glycol monovinyl polyethylene glycol ether (EPEG), acrylic acid (AA), a chain transfer agent, an oxidant and a reducing agent as raw materials, wherein the chain transfer agent is thioglycolic acid (TGA), the oxidant is ammonium persulfate (APS), and the reducing agent is L-ascorbic acid (Vc).
[0115] In this embodiment, the method for preparing the mother solution comprises the following steps:
[0116] (1) Acrylic acid is prepared into liquid A, specifically, acrylic acid is mixed with an appropriate amount of deionized water to prepare liquid A. A chain transfer agent and a reducing agent are prepared into liquid B, specifically, thioglycolic acid, L-ascorbic acid are mixed with an appropriate amount of deionized water, and ultrasonicated for 10 minutes to obtain liquid B.
[0117] (2) Ethylene glycol monovinyl polyethylene glycol ether and ammonium persulfate are placed in a beaker and stirred in a constant temperature magnetic stirrer. The temperature is controlled at 30° C. during the stirring process. After stirring for 1 minute, liquid A and liquid B are added dropwise at the same time using a constant flow pump. The dropping time is controlled at 2 hours to obtain a yellow, thick mother liquor.
[0118] In this embodiment, during the preparation of the mother liquor, the acid-ether ratio of acrylic acid (AA) to ethylene glycol monovinyl polyethylene glycol ether (EPEG) is 5.5:1; the amount of thioglycolic acid (TGA) is 0.8% by mass of ethylene glycol monovinyl polyethylene glycol ether; the amount of ammonium persulfate (APS) is 1.5% by mass of ethylene glycol monovinyl polyethylene glycol ether; and the amount of L-ascorbic acid (Vc) is 0.28% by mass of ethylene glycol monovinyl polyethylene glycol ether.
[0119] In this embodiment, the viscosity of hydroxypropyl methylcellulose is 70000 MPa·s.
[0120] A method for preparing the above-mentioned ultra-fine full tailings filling paste water reducer comprises the following steps: mixing a mother liquor with hydroxypropyl methylcellulose to obtain an ultra-fine full tailings filling paste water reducer.
[0121] An application of the above-mentioned ultrafine full tailings filling paste water reducer in the treatment of ultrafine full tailings filling paste is specifically: the ultrafine full tailings filling paste water reducer is mixed with the ultrafine full tailings filling paste to complete the treatment of the ultrafine full tailings filling paste, wherein the amount of the ultrafine full tailings filling paste water reducer is 0.08% of the total mass of the ultrafine full tailings filling paste.
[0122] In this embodiment, the ultra-fine tailings filling paste is composed of ultra-fine tailings, cement and water, wherein the content of -19 μm particle size in the ultra-fine tailings is 65%, the content of -74 μm particle size is 84%, and the content of D 50 is 10μm.
[0123] The filling paste after adding the water reducing agent in Example 4 was tested, and the results are shown in Table 4.
[0124] Table 4 Test results of filling paste in Example 4
[0125] parameter unit blank Test measurement value Solid concentration % 63 65 Lime-sand ratio - 1:6 1:7 Water reducing agent concentration % 0 0.08 Expansion mm 248 315 7d compressive strength MPa.s 3.36 3.95 28d compressive strength MPa.s 4.17 4.94
[0126] Example 5
[0127] An ultra-fine full tailings filling paste water reducing agent comprises the following raw material components in parts by weight:
[0128] 80 parts of mother liquor,
[0129] Hydroxypropyl methylcellulose 0.12 parts.
[0130] In this embodiment, the mother liquor used is prepared using ethylene glycol monovinyl polyethylene glycol ether as a macromonomer, specifically: it is prepared using ethylene glycol monovinyl polyethylene glycol ether (EPEG), acrylic acid (AA), a chain transfer agent, an oxidant and a reducing agent as raw materials, wherein the chain transfer agent is thioglycolic acid (TGA), the oxidant is ammonium persulfate (APS), and the reducing agent is L-ascorbic acid (Vc).
[0131] In this embodiment, the method for preparing the mother solution comprises the following steps:
[0132] (1) Acrylic acid is prepared into liquid A, specifically, acrylic acid is mixed with an appropriate amount of deionized water to prepare liquid A. A chain transfer agent and a reducing agent are prepared into liquid B, specifically, thioglycolic acid, L-ascorbic acid are mixed with an appropriate amount of deionized water, and ultrasonicated for 10 minutes to obtain liquid B.
[0133] (2) Ethylene glycol monovinyl polyethylene glycol ether and ammonium persulfate are placed in a beaker and stirred in a constant temperature magnetic stirrer. The temperature is controlled at 35° C. during the stirring process. After stirring for 1 minute, liquid A and liquid B are added dropwise at the same time using a constant flow pump. The dropping time is controlled at 1 hour to obtain a yellow, thick mother liquor.
[0134] In this embodiment, during the preparation of the mother liquor, the acid-ether ratio of acrylic acid (AA) to ethylene glycol monovinyl polyethylene glycol ether (EPEG) is 6:1; the amount of thioglycolic acid (TGA) is 1% by mass of ethylene glycol monovinyl polyethylene glycol ether; the amount of ammonium persulfate (APS) is 1.7% by mass of ethylene glycol monovinyl polyethylene glycol ether; and the amount of L-ascorbic acid (Vc) is 0.16% by mass of ethylene glycol monovinyl polyethylene glycol ether.
[0135] In this embodiment, the viscosity of hydroxypropyl methylcellulose is 80000 MPa·s.
[0136] A method for preparing the above-mentioned ultra-fine full tailings filling paste water reducer comprises the following steps: mixing a mother liquor with hydroxypropyl methylcellulose to obtain an ultra-fine full tailings filling paste water reducer.
[0137] An application of the above-mentioned ultrafine full tailings filling paste water reducer in the treatment of ultrafine full tailings filling paste is specifically: the ultrafine full tailings filling paste water reducer is mixed with the ultrafine full tailings filling paste to complete the treatment of the ultrafine full tailings filling paste, wherein the amount of the ultrafine full tailings filling paste water reducer is 0.08% of the total mass of the ultrafine full tailings filling paste.
[0138] In this embodiment, the ultra-fine tailings filling paste is composed of ultra-fine tailings, cement and water, wherein the content of -19 μm particle size in the ultra-fine tailings is 65%, the content of -74 μm particle size is 84%, and the content of D 50 is 10μm.
[0139] The filling paste after adding the water reducing agent in Example 5 was tested, and the results are shown in Table 5.
[0140] Table 5 Test results of filling paste in Example 5
[0141] parameter unit blank Test measurement value Solid concentration % 63 65 Lime-sand ratio - 1:6 1:7 Water reducing agent concentration % 0 0.08 Expansion mm 248 308 7d compressive strength MPa.s 3.36 4.04 28d compressive strength MPa.s 4.17 5.13
[0142] It can be seen from the above results that compared with conventional polycarboxylic acid water reducers, the ultrafine full tailings filling paste water reducer of the present invention has the following advantages: (a) the required synthesis time is short, the reaction temperature is low, and it has good economic benefits. (b) The synthesis steps are simple, it is easily soluble in water, non-toxic and harmless, and friendly to the environment and construction personnel. (c) It can adapt to different types of ultrafine full tailings and has strong versatility. (d) It can significantly increase the concentration of ultrafine full tailings filling paste, reduce the ash-sand ratio, and improve fluidity and strength and operability while greatly reducing water consumption. (e) It can reduce the amount of cement in the ultrafine full tailings filling paste and increase the tailings consumption, while maintaining or improving the slurry performance, which helps to save material costs and tailings treatment costs. It can be seen that the ultrafine full tailings filling paste water reducer of the present invention has the advantages of short synthesis time, low reaction temperature, good economic benefit, good applicability, good operability, and can significantly improve the compressive strength and stability of the filling body. It is a new type of water reducer with excellent performance, which can be widely used in ultrafine tailings filling, can achieve effective filling of ultrafine tailings, has high use value, good application prospects, and is of great significance for achieving cost reduction and efficiency improvement, as well as green sustainable economic development.
[0143] The above embodiments are only preferred implementations of the present invention, and the protection scope of the present invention is not limited to the above embodiments. All technical solutions under the concept of the present invention belong to the protection scope of the present invention. It should be pointed out that for ordinary technicians in this technical field, improvements and modifications without departing from the principle of the present invention should also be regarded as the protection scope of the present invention.
Claims
1. An ultra-fine full tailings filling paste water reducer, characterized in that: The following raw material components are included by weight: 60 to 120 parts of mother liquor, Hydroxypropyl methylcellulose 0.08 to 0.12 parts; The mother liquor is prepared by taking ethylene glycol monovinyl polyethylene glycol ether as a macromonomer; the viscosity of the hydroxypropyl methylcellulose is 60000MPa·s to 80000MPa·s.
2. The ultra-fine full tailings filling paste water reducer according to claim 1, characterized in that: The mother liquor is prepared by taking ethylene glycol monovinyl polyethylene glycol ether, acrylic acid, a chain transfer agent, an oxidant and a reducing agent as raw materials.
3. The ultrafine full tailings filling paste water reducing agent according to claim 2, characterized in that: The acid-ether ratio of acrylic acid to ethylene glycol monovinyl polyethylene glycol ether is 5.5-8.5:0.8-1.2; the amount of the chain transfer agent is 0.6%-1% of the mass of the ethylene glycol monovinyl polyethylene glycol ether; the amount of the oxidant is 1.2%-1.8% of the mass of the ethylene glycol monovinyl polyethylene glycol ether; and the amount of the reducing agent is 0.12%-0.28% of the mass of the ethylene glycol monovinyl polyethylene glycol ether.
4. The ultra-fine full tailings filling paste water reducing agent according to claim 3, characterized in that: The chain transfer agent is at least one of thioglycolic acid, isopropanol, and mercaptoethanol; The oxidant is at least one of ammonium persulfate, hydrogen peroxide, and potassium peroxide; The reducing agent is at least one of L-ascorbic acid, sodium sulfite, ferrous sulfate and sodium bisulfite.
5. The ultrafine full tailings filling paste water reducer according to any one of claims 2 to 4, characterized in that: The preparation method of the mother solution comprises the following steps: (1) preparing liquid A with acrylic acid; preparing liquid B with a chain transfer agent and a reducing agent; (2) Ethylene glycol monovinyl polyethylene glycol ether and an oxidant are mixed and stirred, and liquid A and liquid B are added dropwise to obtain a mother solution.
6. The ultra-fine full tailings filling paste water reducer according to claim 5, characterized in that: In step (1), the liquid A is prepared by mixing acrylic acid with water; the liquid B is prepared by the following method: a chain transfer agent, a reducing agent and water are mixed, and ultrasonicated for 5 minutes to 10 minutes to obtain liquid B; In step (2), the stirring is carried out at a temperature of 20°C to 40°C; the stirring time is 1 min to 3 min; and the dropwise addition time of the liquid A and the liquid B is controlled at 0.5 h to 3 h.
7. A method for preparing the ultrafine full tailings filling paste water reducing agent as claimed in any one of claims 1 to 6, characterized in that: The following steps are involved: The mother liquor is mixed with hydroxypropyl methylcellulose to obtain an ultrafine full tailings filling paste water reducing agent.
8. Use of the ultrafine full tailings filling paste water reducer as described in any one of claims 1 to 6 or the ultrafine full tailings filling paste water reducer prepared by the preparation method according to claim 7 in treating ultrafine full tailings filling paste.
9. The use according to claim 8, characterized in that: The application comprises the following steps: mixing the ultrafine full tailings filling paste water reducer with the ultrafine full tailings filling paste to complete the treatment of the ultrafine full tailings filling paste; the dosage of the ultrafine full tailings filling paste water reducer is 0.06% to 0.08% of the total mass of the ultrafine full tailings filling paste.
10. The use according to claim 9, characterized in that: The ultra-fine tailings filling paste is composed of ultra-fine tailings, cement and water; the content of -19μm particle size in the ultra-fine tailings is greater than 50%, the content of -74μm particle size is greater than 80%, and the content of D 50 <19μm.
Citation Information
Patent Citations
Preparation method of mine tailing filling material
CN107522455A
Method for improving flowability of milltailings and application of method
CN107725106A
Novel preparation method for synthesizing ultrahigh water reducing polycarboxylic acid water reducer from polyether
CN109705282A
Novel expansion filling material and preparation method thereof
CN114455918A
Composite admixture for ultrahigh-concentration full-tailing waste gypsum body
CN117985962A
